Perception of the Cancer Patients on Doctors’ Ability in Breaking Bad News – the Indigenous Adult Cancer Patients’ Perspective in Sarawak, Malaysia - Chang, C.T; Cheah, W.L; Bain, Mathew Gabriel (Researchman Publishers, 2014)
Background and Objectives: Delivering of bad news is an important component of cancer management that can cause long lasting devastating effects for patients and their families if done badly. Materials: This cross-sectional study was conducted among adult cancer patients in indigenous people in a rural community in Sarawak to assess the perceptions of their doctors’ ability in breaking of bad news of their diagnosis. Using snowball sampling method, patients was interviewed face-to-face using The Breaking Bad News Assessment Schedule (BAS). Data was entered and analyzed using SPSS version 19. Results: A total of 61 patients were recruited with majority were female (51.4%), mean age of 52.2 ± 8.0 years. More than half of them suffered from the nasopharynx (52.5%) cancer and 39.3% were in stage 4 of their disease. Mean score for the overall BAS questionnaire was 71.7 ± 14.85 with only 49.2% graded their doctors’ ability on breaking news as “pass” and “outstanding”. The top two questions (reflecting ability) that the respondents perceived as lacking in their doctors were the “use of appropriate body language during interview” (mean= 2.4±1.20), and “management of time available” (mean =2.7 ± 1.05). Conclusion: Structured training and standard protocol should be provided to help doctors to handle breaking of bad news more efficiently, which in return would help the patients to cope better.